Functional Analysis of the Rice Type-B Response Regulator RR22 - Yamburenko, Maria V.; Worthen, Jennifer M.; Zeenat, Asyia; Azhar, Beenish J.; Swain, Swadhin; Couitt, Adam R.; Shakeel, Samina N.; Kieber, Joseph J.; Schaller, G. Eric (Frontiers in Plant Science, 2020)
The phytohormone cytokinin plays a critical role in regulating growth and development throughout the life cycle of the plant. The primary transcriptional response to cytokinin is mediated by the action of the type-B response regulators, with much of our understanding for their functional roles being derived from studies in the dicot Arabidopsis. To examine the roles played by type-B response regulators in a monocot, we employed gain-of-function and loss-of-function mutations to characterize RR22 function in rice. Ectopic overexpression of RR22 in rice results in an enhanced cytokinin response based on molecular and physiological assays. Phenotypes associated with enhanced activity of RR22 include effects on leaf and root growth, inflorescence architecture, and trichome formation. Analysis of four Tos17 insertion alleles of RR22 revealed effects on inflorescence architecture, trichomes, and development of the stigma brush involved in pollen capture. Both loss- and gain-of-function RR22 alleles affected the number of leaf silica-cell files, which provide mechanical stability and improve resistance to pathogens. Taken together, these results indicate that a delicate balance of cytokinin transcriptional activity is necessary for optimal growth and development in rice.